2016
DOI: 10.1039/c6dt02257j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, biological activity, DNA and BSA binding study: novel copper(ii) complexes with 2-hydroxy-4-aryl-4-oxo-2-butenoate

Abstract: A serie of novel square pyramidal copper(ii) complexes [Cu(L)HO] (3a-d) with O,O-bidentate ligands [L = ethyl-2-hydroxy-4-aryl-4-oxo-2-butenoate; aryl = 3-methoxyphenyl-2a, (E)-2-phenylvinyl-2b, (E)-2-(4'-hydroxy-3'-methoxyphenyl)vinyl-2c, 3-nitrophenyl-2d, 2-thienyl-2e] were synthesized and characterized by spectral (UV-Vis, IR, ESI-MS and EPR), elemental and X-ray analysis. The antimicrobial activity was estimated by the determination of the minimal inhibitory concentration (MIC) using the broth microdilutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 81 publications
2
21
0
Order By: Relevance
“…(eg) 4 (a 1 g) 2 (b 1 g) 2 (b 2 g) 1 . The observed values were consistent with square pyramidal geometry which was in agreement with previously reported Cu(II) complexes exhibiting similar geometry …”
Section: Resultssupporting
confidence: 92%
“…(eg) 4 (a 1 g) 2 (b 1 g) 2 (b 2 g) 1 . The observed values were consistent with square pyramidal geometry which was in agreement with previously reported Cu(II) complexes exhibiting similar geometry …”
Section: Resultssupporting
confidence: 92%
“…In Table are presented quenching parameters for 5 , 9–11 [(6.3 ± 0.2) × 10 3 , (5.6 ± 0.2) × 10 3 , (3.1 ± 0.2) × 10 3 , and (5.1 ± 0.1) × 10 3 M −1 , respectively] and these values indicate that the tested compounds have affinity to substitute EB from the EB‐DNA complex and bind strongly with DNA through intercalation. Also, measured K sv clearly indicated that these values are in order with the constants obtained for potential metal‐drugs …”
Section: Resultssupporting
confidence: 62%
“…Since some compounds may show delayed toxicity, it is concluded that the analysis of cytotoxicity should be performed after an interval of at least 48 hours [20]. Therefore, we chose to analyze cytotoxicity after 72 hours similarly to previous experiments [21][22][23].…”
Section: Resultsmentioning
confidence: 99%